Unveiling the perils and catastrophic vulnerabilities of cyber security attacks in accounting / Marjan Mohd Noor and Norshimah Abdul Rahman - Mohd Noor, Marjan; Abdul Rahman, Norshimah (Fakulti Perakaunan, 2023)
The field of cyber security is indeed constantly evolving, with new challenges and threats every year. It is crucial in the cyber realm, which is an entity made up of bits, to both protecting and enabling the defence of secret data and information. Using cutting-edge digital technology and their extraordinary, interconnected capabilities, cyber threat attacks become a reality. As a result, the term "cyber security" can be used to refer as a body of knowledge about the technologies, procedures, and practises used to safeguard computer systems, networks, or programmes as well as data stored in cyberspace against assault, damage, or unauthorized access (Li & Liu, 202 I).